A qualitative investigation of leisure benefits for social and psychological health among international volleyball players living in South Korea - Suh, Y. I.; Kim, J.; Lee, S.; Han, S.; Park, S.-H. (International Journal of Qualitative Studies on Health and Well-being, 2022)
Purpose: The proportion of foreign players in global sports industries has steadily increased in the last decade. This qualitative study aims to capture the benefits of leisure activities for the social and psychological health of international volleyball players affiliated with South Korean volleyball leagues. Method: A purposeful criterion sampling strategy was employed in this qualitative study. Findings: Based on semi-structured interviews with 12 participants, in this study three major themes pertaining to leisure benefits are identified: (a) new leisure opportunities and coping, (b) inter-intra group friendships, and (c) acculturation. Conclusions: These benefits can contribute to social and psychological health for the participants. Practical implications of this study and suggestions for health professionals, sports psychologists, and team counsellors are discussed.